The Rainbow Land: Exploring How Children Accept Diversity - Jossy Vania Christiani (Institute of Research and Community Outreach - Petra Christian University, 2018)
For years, cases related to intolerence of races, religions, and ethnicities have been used for political weapons in Indonesia. This cases has affected children's point of view and behaviour on diversity around them. In order to help not only children, but also parents and educators to be aware of it, I created a 70 minute play for children that discusses how children tolerate differences. I use Indonesia's folktales characters as my characters, and also use Indonesia as the setting. The first main character of the story, Nawang Wulan, struggles on how she tries to be accepted by her new friends who are different from her. While the other main character, Bawang Merah, insisting on excludes Nawang Wulan from her groups because she feels insecure of Nawang Wulan's differences. At the end of the story, Nawang Wulan finally learns that she has to accept her friends' differences first to be accepted. While Bawang Merah finally learns that even though Nawang Wulan is different, her differences are not a threat for her. I use theory of Diversity and Differences in childhood stageand also the theory of inferiority to justify my characters' behavior towards the conflicts. Through this creative work, I want to raise an awareness that diversity is inevitable, even around children. Therefore, it is better for them to learn how to tolerate it so they can accept it rather than misused it.